Pelatihan Penyusunan Laporan Keuangan Bagi Pengurus Koperasi di Kota Sukabumi - R Taufik Hidayat; Keri Boru Hotang (Universitas Muria Kudus, 2022)
Cooperatives are legal entities established by individuals or legal entities. Cooperatives are one of the backbones of the Indonesian economy. In running its business the cooperative compiles financial statements consisting of a balance sheet, income statement, cash flow and notes financial statemets. The financial statements function as a information presented by the entity to interested parties (stakeholders) in making economic decisions. Training in preparing financial reports for Cooperatives in Sukabumi City expected to increase the value of the information presented so that it can be used as a tool in decision making.